Lipid levels of healthy adults in Jaffna district, Northern Province of Sri Lanka: An analysis of secondary data - Thiyahiny, S.N.; Gajanthan, R.; Janahan, R.; Sujanitha, V.; Sivansuthan, S.; Kesavan, R. (The Jaffna Medical Association, 2024)
Abnormal lipid profile is considered as an important contributor to cardiovascular diseases among South Asians. Sri Lanka is a multiethnic South Asian nation and differences in ethnicity may influence the pattern of lipid profile. The aim of this paper is to analyse the lipid levels of healthy adults of a predominantly Sri Lankan Tamil population in the Northern Sri Lanka and compare it with the lipid levels of different ethnic groups reported in the literature. It was a cross-sectional analysis of secondary data of 500 healthy adults who were the controls of a larger study on the lipid profile of diabetic and non-diabetic patients. Cut-off values for desirable lipid levels used in this study were determined according to national and international guidelines. Chi-squared test, independent t-test/ Mann– Whitney U-test and one-way analysis of variance were used to determine the statistical significance and a p-value <0.05 was considered significant. The majority (61.4%) were women and the mean age was 54.8±12.6 years. Mean lipid levels were within normal range except HDL cholesterol (HDL-C) in women (46.6± ±10.6 mg/dL). Desirable lipid levels were observed in majority of the participants (58%- 80%) except HDL-C among women (32%). Half of the study population had a desirable total cholesterol: HDL-C ratio (50.8%). Significant difference between men and women was observed for HDL-C (p<0.05). The HDL-C levels and total cholesterol: HDL-C ratio of Jaffna population were comparable to those of South Asian populations. Further studies are needed to determine the clinical implication of these observations.
Keywords: Lipid level; HDL cholesterol; Jaffna population; South Asians